EP450 The use of indocyanine green in gynae-oncology, beyond sentinel pelvic lymph nodes. (1st November 2019) - Graham, M; Craig, E; Harley, I; Armstrong, A; Dobbs, S; Nagar, H
Abstract : Introduction/Background: Indocyanine Green (ICG) is a fluorescent imaging agent which can be given intravenously or subcutaneously and detected using near-infrared light at laparoscopy. It can be injected para-cervically in order to identify pelvic sentinel nodes at laparoscopy. It can also be given intravenously in order to test tissue perfusion. Methodology: In this study we have reviewed the use of this technology beyond pelvic sentinel nodes. We have identified four interesting cases for discussion. Case 1 - A total laparoscopic Hudson's, pelvic and para-aortic node dissection, omentectomy with re-anastomosis and loop ileostomy was performed for endometrioid adenocarcinoma detected during prior excision of endometrioma. Following this procedure intravenous ICG was used to test perfusion at the bowel anastomosis. Case 2 - A total Laparoscopic hysterectomy was performed for Stage 1A endometrial cancer in a patient with a previous renal transplant. Following the procedure intravenous ICG was used to test perfusion to the transplanted kidney. Case 3 - A Laparoscopic trachelectomy and pelvic node dissection was performed for 1B cervical cancer with incomplete margins. Following this procedure intravenous ICG was used to test uterine perfusion. Case 4 - Open groin node dissection was performed on a patient with a squamous vulval cancer. Using the technology in the open setting, following subcutaneous injection of ICG around the tumor we were able to identify the sentinel groin node. Results: We will show edited operative video of all cases mentioned above. Conclusion: ICG technology has been shown to be a useful adjunct when performing sentinel node sampling. Through this presentation we have discussed a number of other interesting applications in the field of gynae-oncology. Disclosure: Nothing to disclose.